International relations - Tight, Malcolm (International perspectives on higher education research, 2005)
This is the third volume of "International Perspectives on Higher Education Research", a series which aims to feature something of the variety of research being undertaken into higher education systems and issues outside of North America. The theme of this volume is international relations, or how students, academics, universities and higher education systems relate to each other across international borders. The book deliberately sets out to convey a diversity of ideas and approaches. Thus, it includes contributions from researchers working in Australia, Mexico, the Netherlands, New Zealand and the United Kingdom; examples of quantitative and qualitative strategies for data collection and analysis; and methodological approaches ranging from historical and policy analysis to self reflection. What is being considered under the theme of international relations has also been kept deliberately broad. Thus, the eleven chapters in the book examine the movement across borders and between systems of not only students and academics, but also policies and ideas. The book is edited by Malcolm Tight, Professor of Higher Education at Lancaster University in the United Kingdom.